Collaborative optimization path of the "water-carbon-ecology" system in the Yellow River Basin: spatio-temporal evolution and driving factors - Li, Jinhang; Han, Yuping; Zhao, Mengdie; Jiang, Zhuo (Frontiers in Ecology and Evolution, 2025)
Aiming at the increasingly serious problem of water resources shortage and ecological environment deterioration in the world, this study takes 9 provinces and regions in the Yellow River Basin (YRB) as the research objects, and constructs a multi-dimension assessment framework of Water-carbon-ecology (W-C-E) system based on water resources, carbon emissions and ecosystem data from 2002 to 2017. The analysis is innovatively carried out at three progressive levels: first, the independent abundance of each system is assessed, then the coordination between the two systems is examined, and finally the overall robustness of the three systems is measured. Based on this framework, the water-carbon-ecological coupling index (WCENI) is proposed as a comprehensive evaluation index, and the coupling mechanism of the system is deeply analyzed by combining the obstacle degree model and the geographical detector model. The results show that: in terms of time dimension, the overall WCENI increased significantly from 0.3371 to 0.3571 during the study period, and the system coordination index and robustness index showed a steady growth trend. In terms of spatial dimension, there are significant differences in sub-system abundance among provinces and regions, among which Henan Province ranks first with an average WCENI value of 0.3995. The mechanism analysis showed that there was obvious synergistic enhancement effect among the driving factors, and the interaction intensity was significantly higher than that of the single factor, and the per capita water consumption (13.82% obstacle degree) was identified as the key limiting factor restricting the coordinated development of the system. This study not only provides a new analytical framework for understanding the complex human-land system coupling mechanism, but also provides a scientific basis for the implementation of ecological protection and high-quality development strategies in the Yellow River Basin, especially emphasizing the core role of optimizing water resources management in promoting regional sustainable development.